2010
DOI: 10.1016/j.mrgentox.2009.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking during pregnancy: Chromosome translocations and phenotypic susceptibility in mothers and newborns

Abstract: The effects of maternal cigarette smoking during pregnancy on structural chromosome aberrations were evaluated in peripheral lymphocytes from 239 mothers and their 241 newborns to determine whether smoking during pregnancy, genetic susceptibility, and race are associated with chromosome aberrations including translocations. Demographic information and cigarette smoking data were obtained via questionnaire. There were 119 Caucasian Americans, 118 African Americans, and 2 Asian Americans. The average maternal ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
11
2
Order By: Relevance
“…These results clearly show that this current study has enough statistical power to confirm a known response. Cigarette smoking has been previously shown to increase the frequencies of chromosome aberrations (4) but not every study has observed this effect, e.g., (22) and we did not observe a smoking effect here.…”
Section: Discussioncontrasting
confidence: 65%
“…These results clearly show that this current study has enough statistical power to confirm a known response. Cigarette smoking has been previously shown to increase the frequencies of chromosome aberrations (4) but not every study has observed this effect, e.g., (22) and we did not observe a smoking effect here.…”
Section: Discussioncontrasting
confidence: 65%
“…Spearman correlation coefficient was used for bi-variate associations between quantitative variables. Because we noted that the variance of both translocations and stable aberrations increased with their means, we used negative binomial regression models to examine the association between chromosomal aberration and translocation frequencies in cord blood and prenatal air PAHs, with and without control for child’s sex, ethnicity (Dominican vs. African-American) and smoking status at home[16]. Prenatal airborne PAH levels had a skewed distribution and were logarithmically transformed in order to meet assumptions for T-tests and to reduce the impact of extreme values when used as the main predictor in the models for predicting chromosomal aberration frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Other smaller studies also analyzed the genomic frequencies of translocations in newborns [13,[15][16][17]. Recently, a study was published evaluating the effect of maternal smoking during pregnancy on structural chromosome aberrations in 241 newborns [18].…”
Section: Introductionmentioning
confidence: 99%